Delaying the implementation of Payment by Results in mental health: the application of standardisation. Issue 3 (14th September 2015) - Wang, Ruoxi; Shaw, Ian; Middleton, Hugh
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to explore the issues surrounding a long planned expansion of Payment by Results (PbR) into mental health services and to highlight the factors responsible for the delay. Design/methodology/approach – PbR relies upon "standardisation" of conditions and treatments. This depends upon a scheme of classification that can realistically predict resources required to execute treatment of any one case. Plans to fund NHS mental health services on the basis of tariffs derived in this way have been delayed, and a key reason is the lack of high-quality data. This would require effective "standardisation-to the-average" of both a system of classification and a repertoire of costed treatment pathways. This paper investigated the delay implementation by exploring the difficulties in applying standardisation principles to service provision and tariff calculation. Findings – The paper identified the fundamental difficulty with PbR's implementation in applying "standardisation" to practice. This is defining the mental disorder that the patient is suffering and designing care pathways at clinical level considering the balance between practical applicability and conceptual/constructional validity. This is necessary to enable the calculation of a national tariff. The conceptual flaws of the Health of the Nation Outcome Scale led to the constructional shortcomings which compromised the credibility and validity of Mental Health Clustering Tool regarding making accurate classification in a standardised way. The validity and credibility of calculating a national tariff thus became contentious on the basis of this inaccurate clinical classification system. Originality/value – This paper explored the driving factors of delay in implementing PbR in mental health through connecting the recent reform with the fundamental assumptions of "standardisation-to the-average", which provided another perspective to illustrate the current obstacles.